2001
DOI: 10.1287/isre.12.3.322.9710
|View full text |Cite
|
Sign up to set email alerts
|

Research Report: Modifying Paradigms—Individual Differences, Creativity Techniques, and Exposure to Ideas in Group Idea Generation

Abstract: I n today's networked economy, ideas that challenge existing business models and paradigms are becoming more important. This study investigated how individual differences, groupware-based creativity techniques, and ideas from others influenced the type of ideas that individuals generated. While individual differences were important (in that some individuals were inherently more likely to generate ideas that followed the existing problem paradigm while others were more likely to generate paradigm-modifying idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
1
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 49 publications
(58 reference statements)
4
140
1
11
Order By: Relevance
“…Scott and Bruce (1994) use data on 172 engineers, scientists, and technicians in the R&D facility of a large US corporation and find a negative correlation between a self-assessed systematic problemsolving style of these individuals and superiors' assessment of their inventive performance. Based on data derived from an experiment, Garfield et al (2001) find that an intuitive cognitive thinking style positively correlates with generation of paradigm-modifying rather than merely novel ideas.…”
Section: Empirical Studies On Inventive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Scott and Bruce (1994) use data on 172 engineers, scientists, and technicians in the R&D facility of a large US corporation and find a negative correlation between a self-assessed systematic problemsolving style of these individuals and superiors' assessment of their inventive performance. Based on data derived from an experiment, Garfield et al (2001) find that an intuitive cognitive thinking style positively correlates with generation of paradigm-modifying rather than merely novel ideas.…”
Section: Empirical Studies On Inventive Performancementioning
confidence: 99%
“…Even studies on the drivers of inventive performance that link patent data with survey evidence include very few individual characteristics (Hoisl, 2007;Mariani and Romanelli, 2007;Hoisl, 2009;Gambardella et al, 2012;Schettino et al, 2013). Therefore, leaving aside a few small-scale studies, we know only little about the individual-level determinants of inventive performance (Scott and Bruce, 1994;Garfield et al, 2001;Dewett, 2007;Mieg et al, 2010). Our analysis shows that educational level, skills acquired during the career, personality traits such as the Big 5 and risk tolerance, career motivations, cognitive abilities, and cognitive problem-solving style, have high predictive power for inventive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Providing some support for the relationship between cognitive style and paradigm-relatedness, research that assessed paradigmrelatedness in idea generation found that more innovative individuals did tend to generate more paradigm-modifying ideas than more adaptive individuals. 23 However, the same study found that cognitive style was not the only aspect that influenced paradigm-relatedness, as exposing individuals to either paradigm-preserving or paradigm-modifying example ideas also influenced those individuals to generate more ideas of that particular type. 23 So although cognitive style may play a role in the types of ideas that designers generate, there is still opportunity for interventions or situational characteristics to have an influence as well.…”
Section: Paradigm-relatednessmentioning
confidence: 97%
“…[23][24][25] To the best of our knowledge, the role of the problem statement itself has not been studied directly. As we have detailed in our previous research, 26 there are many features of problem statements that can be framed in different ways to influence the approach taken by the designer.…”
Section: Design Problem Framingmentioning
confidence: 99%
See 1 more Smart Citation